The acute impact of extended aerobic exercise on cognitive performance - Tichiwanhuyi, Tendayi Stephen (Rhodes University, Faculty of Science, Department of Human Kinetics and Ergonomics, 2015)
Previous research has established a relationship between exercise and cognition, with more emphasis on this ascertained link, being made on the effects of long term and endurance exercise on cognition. However, enhanced worker effectiveness relies on a strong acute collaboration of physical and cognitive performance during task execution. As a result, the purpose of this study was to examine the acute effects of extended aerobic exercise on visual perception, working memory and motor responses, and to achieve this 24 participants (12 males and 12 females) aged between 18 and 24 participated in a 2 bout cycling exercise. The experimental condition had cycling resistance set at 60 percent of each individual's maximum aerobic output and the control condition had zero cycling resistance, where three cognitive tasks were performed at 10 minute intervals during the cycling exercise. The results showed that exercise did not affect any significant changes on the cognitive performance measures over the entire cycling duration, as well as during the exercise phase (cycling with resistance). However, visual perception improved significantly (p<0.05) immediately after exercise. This led to the conclusion that moderate to high intensity exercise when performed for an extended duration, has selective effects on certain cognitive performance measures, with the time at which the performance is measured during the exercise being a relevant factor to be considered for maximum activation effects of the exercise.
Keywords: Aerobic exercises; Cognition -- Effect of exercise on; Exercise -- Physiological aspects; Exercise -- Psychological aspects; Visual perception; Short-term memory; Motor ability; Human information processing